EFFICACY OF REGIONAL FLAPS FOR RECONSTRUCTION OF THE MOUTH CAVITY FLOOR AFTER ONCOLOGICAL RESECTIONS - Kravets, O.V.; Shypko, A.F.; Burtyn, O.V.; Kopchak, A.V.; Khlynin, A.V.; Guryanov, V.G. (World of Medicine and Biology, 2022)
In the study, a sequential analysis is presented on the efficacy of various types of regional flap replacement, on the replacement of superficial and deep defects of the mouth floor after oncological resections. It has been shown that the use of a platysma musculocutaneous flap to replace surface defects of the oral cavity floor increases the duration of surgery, but significantly improves the functional status in terms of the completeness of the diet, public nutrition and the quality of life of patients in terms of appearance, chewing and general quality of life in indices of appearance, congestion and the general quality of life comparing to the use of the nasolabial flap. The use of a pectoralis major myocutaneous flap to replace deep defects of the oral cavity floor also increases the duration of the surgical intervention, but significantly improves the functional status according to the indices of the completeness of the diet, public nutrition and the quality of life in patients according to the indices of appearance, chewing, mood and general quality of life in comparison with the use of the sternocleidomastoid myocutaneous flap.